PENGARUH HARGA, CITRA MEREK DAN BRAND AMBASSADOR TERHADAP KEPUTUSAN PEMBELIAN PRODUK BRODO : (Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Bhayangkara Jakarta Raya Angkatan 2020-2022) - Muhammad Kamil Hafidzi; Murti Wijayanti; Doddy Kurniawan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The research carried out aims to determine simultaneously and partially the independent variables, namely price, brand image and brand ambassador, the dependent variable for purchasing decisions. The method used in this research is a quantitative method, where this research uses calculations using the Hair Technique. The population in this study were students at Bhayangkara University, Jakarta Raya, Faculty of Economics & Business, Study Program Class 2020-2022 with a sample of 119 respondents. Before analyzing the data, 30 respondents were used as a pilot study to determine the feasibility of this research with the help of the SPSS version 25 program. Based on the research results: 1) the independent variable Price has a significant positive influence on Purchasing Decisions, 2) the Brand Image variable has a significant positive influence on Purchasing Decisions, 3) the Brand Ambassador variable has a significant positive influence on Purchasing Decisions and 4) the variables Price, Brand Image and Brand Ambassador simultaneously influence purchasing decisions.